Identity, Language, and Cultural Integration: Studying Romanian From an Intercultural Perspective - Mocanu, Lăcrămioara; Cărăuș, Ancuța Loredana; Cernei, Carolina (Didactica Danubiensis, 2026)
This article studies the complex relationship between identity, language, and cultural integration in the context of Romanian language learning among speakers of other languages. Based on the premise that language is not just a communication tool but a vital vector of cultural and social identity, the study analyzes how the process of language acquisition intersects with the formation of personal and collective identity in the Romanian space. The article, by examining contemporary intercultural theories and the socio-linguistic realities of Romania, highlights the challenges and opportunities associated with studying the Romanian language in a globalized, multi-ethnic, and multicultural context. It examines the pragmatic, psychological, and social aspects of language learning as a two-dimensional process: on the one hand, the acquisition of language skills necessary for functional integration, and on the other hand, the formation of a cultural identity between one's own heritage and the new Romanian cultural reality. The conclusions highlight the need for a holistic approach to teaching Romanian as a foreign or second language, which integrates not only grammatical and lexical aspects, but also cultural, pragmatic, and identity dimensions of communication.